The Influence of Market Orientation and Entrepreneurial Orientation on the Marketing Performance of Msmes in Deket Sub-District - Bella Fernanda; Evi Fitrotun Najiah; Mohammad Yaskun (Sean Institute, 2024)
The purpose of this study is to determine the influence of market orientation and entrepreneurial orientation on the marketing performance of MSMEs in Deket sub-district partially or simultaneously and the most dominant factors. Using the quantitative method The population in this study, namely MSMEs in Deket District, amounted to 98 samples taken from a total population of 4,581. The results of the analysis showed that all the data collected had good validity and reliability, there were no problems of multicollinearity or heteroscedasticity. The output of SPSS shows that the determination coefficient (R2) is 0.219. Based on the calculation of the t-table, the calculated t-value for the variable X1 is 2.730, and for the variable X2 is 3.420, exceeding the t-table value by 1.985, suggesting that the two have a partial or stand-alone influence. In addition, the result of the calculation f calculation was 13.289, exceeding the f-value of the table by 3.090, indicating that there was a simultaneous or joint influence of the two variables. The results of the multiple linear regression analysis showed that the resulting formula was Y = 7.372 + 0.393 X1 + 0.012 X2.